2022
DOI: 10.1161/jaha.121.025470
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Particle Radioactivity (Gross β Activity) and Particulate Matter ≤2.5 μm Aerodynamic Diameter on Cardiovascular Disease Mortality

Abstract: Background Although the effects of fine particulate matter (particulate matter ≤2.5 μm aerodynamic diameter [PM 2.5 ]) on cardiovascular disease (CVD) morbidity and mortality are well established, little is known about the CVD health effects of particle radioactivity. In addition, there are still questions about which of the PM 2.5 physical, chemical, or biological properties are mostly responsible for its toxicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Gamma radiation, a high-energy electromagnetic wave, is produced by nuclear reactions and has strong penetrative capabilities; therefore, external exposure can cause significant harm. For example, recent studies have shown that known associations between fine particulate matter (PM 2.5 ) and health are modified by gross activity (a measure of the counts of ray per unit time) (Blomberg et al, 2019 ; Dong et al, 2022 ). In the present study, we leverage statistical and ML methods to simultaneously consider the effects of background radiation levels (gamma radiation emitted from airborne radioactive particles and indoor radon gas), PM 2.5 exposure, and other social and behavioral factors on county-level lung cancer rates.…”
Section: Introductionmentioning
confidence: 99%
“…Gamma radiation, a high-energy electromagnetic wave, is produced by nuclear reactions and has strong penetrative capabilities; therefore, external exposure can cause significant harm. For example, recent studies have shown that known associations between fine particulate matter (PM 2.5 ) and health are modified by gross activity (a measure of the counts of ray per unit time) (Blomberg et al, 2019 ; Dong et al, 2022 ). In the present study, we leverage statistical and ML methods to simultaneously consider the effects of background radiation levels (gamma radiation emitted from airborne radioactive particles and indoor radon gas), PM 2.5 exposure, and other social and behavioral factors on county-level lung cancer rates.…”
Section: Introductionmentioning
confidence: 99%